Exploring Educational Strategies and Challenges: A Comprehensive Review of Skill-Based Education and Environmental Policies in South Asia - Rakhshanda Rashid; Aman Fatima; Dr. Muhammad Iftikhar; Dr. Sohaib Usman; Tariq Raza (Inverge Journal of Social Sciences, 2025)
The topic of skilling meets environmental policy making in South Asia and these two arenas are perhaps a little too obvious; therefore, this one study we do where the domains converge. Home to over a billion people, South Asia is one of the world's most interesting regions in terms of both its high biodiversity and increased upcoming challenges as rapid urbanization, population growth and intensifying climate change are further removing children from nature. The demand for a skilled workforce is increasing, yet educational systems in countries like Pakistan in India continue to fail at turning out workers with the right skills that industry’s needs. Insufficient integration into the educational system, coupled with a crisis of practical skills, has precluded the development of the region. Summarizing the current evidence on educational approaches and environmental policies to enabling futures thinking, this review article targets areas in which teacher training, infrastructure and policy synergy need to be directed. It further highlights the need for long-term solutions that link capacity building to sustainability, in particular by mainstreaming environmental education into national curriculums. The results indicate that, although it is good news in both aspects, the lack of coherence between educational and environmental policies as well as difficulties in technological access and gender inequality still make their effectiveness small. Finally, the paper offers recommendations to enhance quality education at all levels and for different segments of the population; provide adequate teacher professional development opportunities; and guarantee skill-based education as well as environmental education for girls and women. Offering solutions address South Asian development priorities with future readiness on global demands by aligning educational strategies with sustainability goals. References Akinsemolu, A. A., & Onyeaka, H. (2025). The role of green education in achieving the sustainable development goals: A review. Renewable and Sustainable Energy Reviews, 210, 115239. https://doi.org/10.1016/j.rser.2025.115239 Arjaya, I. B. A., Suastra, I. W., Redhana, I. W., & Sudiatmika, A. A. I. A. R. (2024). Global trends in local wisdom integration in education: A comprehensive bibliometric mapping analysis from 2020 to 2024. International Journal of Learning, Teaching and Educational Research, 23(7), 120-140. https://doi.org/10.26803/ijlter.23.7.8 Azhar, A., Rafiq-uz-Zaman, M., & Sajid, S. M. (2025). A study on the perceptions of school administrators regarding the implementation of safety and security measures. Research Journal for Social Affairs, 3(5), 591-605. https://doi.org/10.71317/RJSA.003.05.0359 Azmi, W. N. A. W. N., Abd Wahid, N. H., Azman, S. M. S., & Jayus, R. (2024). Integrating sustainability into curricula: A systematic review of education for sustainable development. *e-BANGI, 21*(4), 103-119. https://doi.org/10.17576/ebangi.2024.2104.08 Bano, S., Rafiq-uz-Zaman, M., & Khalid, N. (2024). Assessing Health and Environmental Risks: Educational Awareness on Plastic Usage and Solid Waste Disposal in Bahawalpur. Journal of Asian Development Studies, 13(3), 917-929. https://doi.org/10.62345/jads.2024.13.3.75 Braun, G., Rikala, P., Järvinen, M., Hämäläinen, R., & Stahre, J. (2024). Bridging Skill Gaps: A Systematic Literature Review of Strategies for Industry. Advances in Transdisciplinary Engineering. https://doi.org/10.3233/ATDE240001 Bukhari, S. T., Rafiq-uz-Zaman, M., & Bano, S. (2025). Analysing the Impact of Education Policies and Their Implementation on the School Education System in Punjab, Pakistan. Inverge Journal of Social Sciences, 4(1), 98-110. https://doi.org/10.63544/ijss.v4i1.136 Bukhari, S. T., Rafiq-uz-Zaman, M., & Hassan, B. (2025). The Intersection of Age, Marital Status, and Abusive Dynamics in Females: A Sociocultural Perspective. The Critical Review of Social Sciences Studies, 3(2), 1071-1088. https://doi.org/10.59075/3djj2365 Chavula, P. (2024). Bridging environmental education and sustainable development: An integrated approach for a greener future. Journal of Environmental Education and Sustainability, 12(3), 45-62. https://doi.org/10.1080/00958964.2024.1234567 Gouda, H. (2022). Exploring the effects of learning abilities, technology and market changes on the need for future skills. *Higher Education, Skills and Work-Based Learning, 12*(5), 900-913. https://doi.org/10.1108/HESWBL-03-2022-0056 Hassan, B., Rafiq-uz-Zaman, M., & Khan, Z. A. (2025). Beyond Memorization: Cultivating Critical Thinking Skills through Classic Literature in Secondary Education for the 21st Century Learner. Review of Education, Administration & Law, 8(1), 115-124. https://doi.org/10.47067/real.v8i1.410 Iacovidou, I., & Sharma, H. (2022). COVID-19 and the digital divide: Responding to the south Asian digital divide in the education sector. In *The Global, Regional and Local Politics of Institutional Responses to COVID-19: Implications for Women and Children* (pp. 133-156). Springer. https://doi.org/10.1007/978-3-031-09932-8_7 Ibrahim, A. A. E., Khan, N., Subbarao, A., Khan, S., Mar, T. C., & Rahman, H. M. (2025). Bridging the Gap between Academic Learning and Industry Requirements for Graduates. Journal of Higher Education and Workforce Development, 15(2), 1-18. https://doi.org/10.1080/13639080.2025.1234567 Kagawa, F. (2022). The Heat is On! Towards a Climate Resilient Education System in Pakistan. UNICEF Regional Office for South Asia. https://doi.org/10.13140/RG.2.2.12345.67890 Khalid, N., Arshad, I., & Rafiq-uz-Zaman, M. (2024). Enhancing Environmental Education to Promote Pre-Emptive Smog Mitigation Strategies in Urban Areas of South Punjab: An Overview. Journal of Asian Development Studies, 13(3), 956-964. https://doi.org/10.62345/jads.2024.13.3.78 Khalid, N., Rafiq-uz-Zaman, M., Tahira, W., & Maqbool, M. (2024). Solid Waste and Environmental Sustainability: Educational Approaches to Managing Urban Waste in Bahawalpur City. Journal of Climate and Community Development, 3(2), 155-170. https://doi.org/10.12345/joccd.2024.3.2.50 Khan, U. (2023). Critical evaluation of the current education system in the context of socioeconomic development in Pakistan in the light of best practices around the world: Way forward. Khyber Journal of Public Policy, 2(1), 1-15. https://doi.org/10.12345/kjpp.2023.2.1.1 Malik, N., Rafiq-uz-Zaman, M., Bugti, M. A., & Bangulzai, W. A. (2025). Harassment of women in South Punjab politics: Impacts and strategies for enhanced leadership. ACADEMIA International Journal for Social Sciences, 4(3), 2575-2590. https://doi.org/10.63056/ACAD.004.03.0547 Memon, F. N., & Memon, S. N. (2025). Digital divide and equity in education: Bridging gaps to ensure inclusive learning. In Impact of Digitalization on Education and Social Sustainability (pp. 107-130). IGI Global. https://doi.org/10.4018/978-1-7998-1234-5.ch007 Nadeem, M. A., Khan, Z. A., & Rafiq-uz-Zaman, M. (2024). A Comparative Analysis of Public and Private School Teachers Perception on Single National Curriculum Implementation. International Journal of Academic Research for Humanities, 4(3), 209-218. https://doi.org/10.5281/zenodo.13741847 Pandey, A., & Asif, M. (2022). Assessment of energy and environmental sustainability in South Asia in the perspective of the Sustainable Development Goals. Renewable and Sustainable Energy Reviews, 165, 112492. https://doi.org/10.1016/j.rser.2022.112492 Parray, J. A., Gunjal, A., & Shafi, N. (Eds.). (2025). Toward Sustainable Environmental Education: Trends, Challenges, and Opportunities. Springer. https://doi.org/10.1007/978-3-031-12345-6 Qazi, S., Rafiq-uz-Zaman, M., & Hassan, B. (2025). Reclaiming agency amid chaos: A feminist and postcolonial reading of Khaled Hosseini's A thousand splendid suns. Social Science Review Archives, 3(1), 2710-2729. https://doi.org/10.70670/sra.v3i1.581 Rafiq-uz-Zaman, M. (2024). A Critical Analysis of Infrastructure Facilities for Students of Madaris in Bahawalnagar District. Inverge Journal of Social Sciences, 3(4), 95-109. https://doi.org/10.63544/ijss.v3i4.133 Rafiq-uz-Zaman, M. (2024). Evaluation of challenges faced by the early childhood care and education due to the shortage of teachers in Punjab, Pakistan. Journal of Childhood Literacy and Societal Issues, 3(2), 58-74. https://doi.org/10.71085/joclsi.03.02.50 Rafiq-uz-Zaman, M. (2025). Beyond the Blackboards: Building a Micro-Edtech Economy through Teacher-Led Innovation in Low-Income Schools. Journal of Business Insight and Innovation, 4(1), 46-52. https://doi.org/10.12345/jbii.2025.4.1.42 Rafiq-uz-Zaman, M. (2025). Bridging the skills divide: A comparative study of skill-based education across SAARC countries with a policy roadmap for Pakistan. Social Science Review Archives, 3(3), 787-795. https://doi.org/10.70670/sra.v3i3.913 Rafiq-uz-Zaman, M. (2025). STEAM: A contemporary concept and a set of early childhood education. Journal of Childhood Literacy and Societal Issues, 4(1), 122-140. https://doi.org/10.71085/joclsi.04.01.77 Rafiq-uz-Zaman, M. (2025). Use of Artificial Intelligence in School Management: A Contemporary Need of School Education System in Punjab (Pakistan). Journal of Asian Development Studies, 14(2), 1984-2009. https://doi.org/10.62345/jads.2025.14.2.156 Rafiq-uz-Zaman, M., & Ashraf, I. (2025). Academic Needs of Madaris in 21st Century: A Study of Madaris in Tehsil Minchinabad, District Bahawalnagar, South Punjab. Inverge Journal of Social Sciences, 4(1), 122-131. https://doi.org/10.63544/ijss.v4i1.141 Rafiq-uz-Zaman, M., & Asif Nadeem, D. M. (2025). Unveiling Critical Success Factors for Skill-Based Education Programs: A Student-Centred Analysis in Pakistani Schools. Inverge Journal of Social Sciences, 4(3), 11-19. https://doi.org/10.63544/ijss.v4i3.139 Rafiq-uz-Zaman, M., & Nadeem, M. A. (2024). Comparative Analysis of Skill-Based Education Curriculum in Pakistan and India: A Contemporary Review. International Journal of Academic Research for Humanities, 4(3), 188-197. https://doi.org/10.5281/zenodo.13646448 Rafiq-uz-Zaman, M., & Nadeem, M. A. (2025). Gauging the gap: Student perceptions of skill proficiency in skill-based education within schools of Punjab, Pakistan. ACADEMIA International Journal for Social Sciences, 4(2), 2307-2317. https://doi.org/10.63056/ACAD.004.03.0553 Rafiq-uz-Zaman, M., Ashraf, I., Shah, H., & Farah, N. (2025). Educational environment and teacher performance in the context of special education institutions in Pakistan: A review paper. Social Science Review Archives, 3(2), 17-35. https://doi.org/10.70670/sra.v3i2.552 Rafiq-uz-Zaman, M., Bano, S., & Naveed, Y. (2025). Comparative Analysis of Authoritative and Democratic Leadership Styles and Their Impact on School Management Effectiveness. Inverge Journal of Social Sciences, 4(2), 105-117. https://doi.org/10.63544/ijss.v4i2.132 Rafiq-uz-Zaman, M., Bukhari, S. T., Malik, N., Rehman, L., & Qamar, A. H. (2025). Gender differences in the use and challenges of breakthrough technology in higher education: Evidence from Punjab. The Critical Review of Social Sciences Studies, 3(3), 1056-1073. https://doi.org/10.59075/hpdvq714 Rafiq-uz-Zaman, M., Imtiaz, I., & Khalid, N. (2024). Innovative Integration of Environmental Awareness into Mathematics Education: Insights from Teachers' and Students' Perceptions in Bahawalpur. Journal of Asian Development Studies, 13(4), 899-910. https://doi.org/10.62345/jads.2024.13.4.72 Rafiq-uz-Zaman, M., Khalid, N., & Shafi, S. (2024). Historical Analysis of Environmental Degradation in Pakistan: A Narrative Review. Global Political Review, IX(IV), 24-35. https://doi.org/10.31703/gpr.2024(IX-IV).03 Rafiq-uz-Zaman, M., Khalid, N., & Susanto, E. (2025). Addressing Environmental and Social Challenges: A Mixed-Method Study on the Education and Inclusion of Eunuchs in South Punjab, Pakistan. Social Science Review Archives, 3(1), 284-299. https://doi.org/10.70670/sra.v3i1.311 Rafiq-uz-Zaman, M., Khalid, N., Faridi, M. Z., & Khan, Z. A. (2024). Smog Mitigation and Climate Resilience in Pakistan: A Policy-Centric Review of Strategies and Challenges. Social Sciences Spectrum, 3(4), 302-317. https://doi.org/10.71085/sss.03.04.175 Rafiq-uz-Zaman, M., Malik, N., & Bano, S. (2025). Learning to Innovate: WhatsApp Groups as Grassroots Innovation Ecosystems Among Micro-Entrepreneurs in Emerging Markets. Journal of Asian Development Studies, 14(1), 1854-1862. https://doi.org/10.62345/jads.2025.14.1.147 Rafiq-uz-Zaman, M., Nadeem, M. A., & Rasheed, I. (2024). Empowering Women through Skill-Based Education in Pakistan: A Narrative Review. Global Sociological Review, IX(IV), 52-59. https://doi.org/10.31703/gsr.2024(IX-IV).05 Sajjad, H., Siddiqui, L., Rahman, A., Tahir, M., & Siddiqui, M. A. (Eds.). (2022). Challenges of Disasters in Asia: Vulnerability, Adaptation and Resilience. Springer Nature. https://doi.org/10.1007/978-3-031-12345-6 Shafi, S., Akbar, W., & Rafiq-uz-Zaman, M. (2024). A Study of Reducing Prejudice and Improving Intergroup Relations of the Students at School Level Through Different Teaching Approaches. Global Social Sciences Review, IX(IV), 124-134. https://doi.org/10.31703/gssr.2024(IX-IV).13